Utilization of cold pressed chia seed oil waste in a low-fat salad dressing as natural fat replacer - Akcicek, Alican; Karasu, Salih (WILEY, 2018)
The main aim of this study is to develop a low-fat salad dressing by using cold-press chia seed oil waste powder (CCWP). Formulation optimization was conducted by response surface methodology (RSM) based on the theological and microstructural properties. All of the samples exhibited non-Newtonian flow behavior, and storage modulus (G') value was higher than loss modulus (G '') in the whole frequency range. The consistency coefficient (K) value of the samples was significantly affected by formulation (p < .05) and found as 0.552-15.87 Pa.s(n). The optimum stabilizer, oil, emulsifier, and CCWP content are 0.33, 10, 1.12, and 2%, respectively. The samples formulated by CCWP showed a high G' and zeta (zeta) potential values at a low oil and emulsifier content. The samples prepared with optimum formulation exhibited high stability and comparable recovery properties with commercial samples. This study suggested that CCWP could be used in a low-fat salad dressing as a fat replacer.
Keywords: SENSORY PROPERTIES; RHEOLOGICAL PROPERTIES; MAYONNAISE; STABILITY; EMULSIONS; MUCILAGE; XANTHAN; Engineering; Food Science & Technology